Electronic Diachronic Corpus and Dictionaries of Old Bulgarian - Ganeva, Gergana (Studia Ceranea, 2018)
The electronic system histdict is designed as a tool for research, adequate presentation and popularization of a part of Bulgaria’s cultural and historical heritage: the Bulgarian language and its medieval literature. The article describes the various steps in the development of histdict. Attention is paid to each component of the resource: specialized Unicode fonts, electronic diachronic corpus, dictionary of Old Bulgarian, historical dictionary equipped with tools for writing and editing dictionary entries, grammatical dictionary, prototypical search engine, and virtual keyboard. The article also lays out the principles followed in the development of the diachronic grammatical dictionary of the Bulgarian language.